The Choice of Hemodialysis Membrane Affects Bisphenol A Levels in Blood - Bosch Panadero, Enrique; Mas, Sebastian; Sánchez Ospina, Didier; Camarero, Vanesa; Pérez Gómez, Maria V.; Sáez Calero, Isabel; Abaigar, Pedro; Ortiz, Alberto; Egido, Jesús; González Parra, Emilio (My University, 2016)
Bisphenol A (BPA), a component of some dialysis membranes, accumulates in CKD. Observational studies have linked BPA exposure to kidney and cardiovascular injury in humans, and animal studies have described a causative link. Normal kidneys rapidly excrete BPA, but insufficient excretion may sensitize patients with CKD to adverse the effects of BPA. Using a crossover design, we studied the effect of dialysis with BPA-containing polysulfone or BPA-free polynephron dialyzers on BPA levels in 69 prevalent patients on hemodialysis: 28 patients started on polysulfone dialyzers and were switched to polynephron dialyzers; 41 patients started on polynephron dialyzers and were switched to polysulfone dialyzers. Results were grouped for analysis. Mean BPA levels increased after one hemodialysis session with polysulfone dialyzers but not with polynephron dialyzers. Chronic (3-month) use of polysulfone dialyzers did not significantly increase predialysis serum BPA levels, although a trend toward increase was detected (from 48.866.8 to 69.1610.1 ng/ml). Chronic use of polynephron dialyzers reduced predialysis serum BPA (from 70.668.4 to 47.167.5 ng/ml, P,0.05). Intracellular BPA in PBMCs increased after chronic hemodialysis with polysulfone dialyzers (from 0.03960.002 to 0.04360.001 ng/106 cells, P,0.01), but decreased with polynephron dia lyzers (from 0.04560.001 to 0.03660.001 ng/106 cells, P,0.01). Furthermore, chronic hemodialysis with polysulfone dialyzers increased oxidative stress in PBMCs and inflammatory marker concentrations in cir culation. In vitro, polysulfone membranes released significantly more BPA into the culture medium and induced more cytokine production in cultured PBMCs than did polynephron membranes. In conclusion, dialyzer BPA content may contribute to BPA burden in patients on hemodialysis